SENSIBILITY ANALYSIS OF THE HALF-SLOPE RATIO IN NON-LINEAR MONOTONE INCREASING BIVARIATE RELATIONSHIPS - Guàrdia i Olmos, Joan; Turbany Oset, Jaume; Freixa i Blanxart, Montserrat (Anales de Psicología / Annals of Psychology)
In the last time, the use of the statistical procedures belonging to the tradition of the Exploratory Data Analysis (EDA) (Tukey, 1977) has promoted a deep interest for the data exploration as a suitable vehicle in order to assure the prospective results. However, some of the proposed indices by EDA, are not been evaluated concerning their statistical sensibility. Our goal is to analyze one of the EDA most suggestive indices, the Half-Slope Ratio method, introduced into the use of the resistant line (Velleman y Hoaglin, 1981). It is used in order to ascertain the possible lineality of the bivariant plot. Through the generation of several non-linear functions, it may be shown first that de Half-Slope Ratio has a very severe behaviour and second, that tendency is more lax in the linear regression model.